DIABETIC LUMBOSACRAL RADICULOPLEXUS NEUROPATHY (DLSRN) AFTER BARIATRIC SURGERY. Issue 12 (15th November 2016) - Connor, Antoinette O'; McNamara, Brian; Sweeney, Brian
Abstract : A 54-year-old type II diabetic presented with a BMI of 46. His obesity proved refractory to conservative measures, and he underwent gastric bypass surgery. His initial post-operative period was uneventful, and he was fully compliant with the recommended diet plan and vitamin supplements. Five months after surgery, having lost 44 kg, he presented with a two month history of marked pain and weakness in the left thigh requiring him to use a pair of crutches. His neurological examination was significant for left quadricipital amyotrophy with reduced power. Initial laboratory work-up was unremarkable. Magnetic resonance imaging of the lumbosacral spine and pelvis was reassuring. Needle EMG showed patchy severe denervation at multiple levels in both lower limbs, left greater than right, consistent with a lumbosarcral plexopathy. Discussion: Obesity has reached epidemic proportions resulting in a growing worldwide demand for bariatric surgery.1 As the frequency of bariatric surgery is increasing, so is the recognition of neurological complications. We report the first case of post bariatric surgery DLSRSN. DLSRN an important diagnosis to consider in every patient with a history of type 2 diabetes who develops a subacute asymmetrical lower limb neuropathy after bariatric surgery.